Third Trimester Fetuses Demonstrate Priming, a Form of Implicit Memory, In Utero - Hanna Gustafsson; Jennifer Hammond; Julie Spicer; Sierra Kuzava; Elizabeth Werner; Marisa Spann; Rachel Marsh; Tianshu Feng; Seonjoo Lee; Catherine Monk (MDPI AG, 2022)
Research examinations of changes in fetal heart rate (HR) to operationalize fetal memory suggests that human memory capacities emerge in utero. However, there is little evidence for a form of implicit memory or priming. The present aim was to determine if priming is evident in utero. Fetal HR, maternal HR and maternal respiratory rate (RR) were examined in 105 women during the third trimester of pregnancy. Women experienced two counterbalanced laboratory tasks, the Stroop task and the paced breathing task, and their cardiorespiratory activity functioned as a stimulus for fetuses. Repeated measures ANOVAs revealed maternal HR increased during the Stroop task but only when the Stroop task was presented first (89.64 bpm to 92.39 bpm) (p = 0.04). Maternal RR increased during the Stroop task, regardless of task order (17.72 bpm to 21.11 bpm; 18.50 bpm to 22.60 bpm) (p < 0.01). Fetal HR increased during the paced breathing task, but only when it followed maternal exposure to the Stroop task (141.13 bpm to 143.97 bpm) (p < 0.01). Fetuses registered maternal HR and RR reactivity to the Stroop task, which influenced their response during maternal engagement with a related task, suggesting priming. Further study of fetal memory may suggest another pathway by which prenatal exposures impact future development.